Direct Costs of COVID-19 Inpatient Admissions in a Portuguese Tertiary Care University Centre - Joana Seringa; Sérgio Pedreiras; Maria João Freitas; Rosa Valente de Matos; João Rocha; Christopher Millett; Rui Santana (Karger Publishers, 2022)
Background: The COVID-19 pandemic has posed greater financial pressure on health systems and institutions that had to respond to the specific needs of COVID-19 patients while ensuring the safety of the diagnosis and treatment of all patients and healthcare professionals. To assess the financial impact of COVID-19 patients admitted to hospitals, we have characterized the cost of COVID-19 admissions, using inpatient data from a Portuguese Tertiary Care University Centre. Methods: We analysed inpatient data from adult patients diagnosed with COVID-19 who were admitted between March 1, 2020 and May 31, 2020. Admissions were eligible if the ICD-10-CM principal diagnosis was coded U07.1. We excluded admissions from patients under 18 years old, admissions with incomplete records, admissions from patients who had been transferred to or from other hospitals or those whose inpatient stay was under 24 h. Pregnancy, childbirth, and puerperium admissions were also excluded, as well as admissions from patients who had undergone surgery. Results: We identified 223 admissions of patients diagnosed with COVID-19. Most were men (64.1%) and aged 45-64 years (30.5%). Around 13.0% of patients were admitted to intensive care units and 9.9% died in hospital. The average length of hospital stay was 12.7 days (SD = 10.2) and the average estimated cost per admission was EUR 8,177 (SD = 11,534), which represents more than triple the inpatient base price (EUR 2,386). Human resources accounted for the highest proportion of the total costs per admission (50.8%). About 92.4% of the admissions were assigned to Diagnosis Related Group (DRG) 723, whose inpatient price is lower than COVID-19 inpatient costs for all degrees of severity. Conclusion: COVID-19 admissions represent a substantial financial burden for the Portuguese NHS. For each COVID-19 hospitalized patient it would have been possible to treat three other hospitalized patients. Also, the price set for DRG 723 is not adjusted to the cost of COVID-19 patients. These findings highlight the need for additional financial resources for the health system and, in particular, for hospitals that have treated high volumes of hospitalized patients diagnosed with COVID-19.